50th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2012
DOI: 10.2514/6.2012-269
|View full text |Cite
|
Sign up to set email alerts
|

Adjoint-based method for supersonic aircraft design using equivalent area distribution

Abstract: This paper describes the efforts in the development of new adjoint-based techniques for the design of supersonic aircraft that must match a target equivalent area distribution at constant lift coefficients. This specific approach is meant to be part of a larger effort to create multidisciplinary analysis and optimization capabilities that can be used to design low-boom supersonic aircraft with adequate aerodynamic and structural performance. The paper focuses on the description of an inverse equivalent area di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…18,19,20 In this study, the selective application of these techniques allows the removal of a lift constraint term that was previously included in Eq. 1.…”
Section: Iib Geometry Modelingmentioning
confidence: 99%
“…18,19,20 In this study, the selective application of these techniques allows the removal of a lift constraint term that was previously included in Eq. 1.…”
Section: Iib Geometry Modelingmentioning
confidence: 99%
“…2 variable nodes C.y0 and E.y0 are both arrays and are directly connected. However, F.y0 is a scalar variable, which depends on a single entry form C.y0, so a subvariable node, C.y0 [2], is added to the graph in between C.y0 and F.y0. By using the subvariable nodes, the computational advantages of problem sparsity are retained.…”
Section: Dependency Graphmentioning
confidence: 99%
“…In them elements of the aircraft are considered both in the isolated state and under conditions of aerodynamic interference. [1][2][3][4] The limited nature of such studies is revealed in the focus on prescribed flight conditions and specific geometrical shapes. This makes it difficult to establish general laws and to use the results obtained to solve similar problems.…”
mentioning
confidence: 99%